Differentiation of bone marrow‐derived cells toward thermogenic adipocytes in white adipose tissue induced by the β3 adrenergic stimulation. Issue 4 (9th January 2019) - Yoneshiro, Takeshi; Shin, Woongchul; Machida, Ken; Fukano, Keigo; Tsubota, Ayumi; Chen, Yong; Yasui, Hironobu; Inanami, Osamu; Okamatsu‐Ogura, Yuko; Kimura, Kazuhiro
ABSTRACT: Bone marrow provides progenitors of several types of cells, including muscle and white adipocytes, ensuring peripheral tissue homeostasis. However, the role of bone marrow‐derived cells (BMCs) in induction of thermogenic adipocytes is unresolved. The purpose of this study is to examine whether BMCs are involved in the emergence of thermogenic adipocytes through adrenergic activation. Irradiation of mice with 8 Gy of X‐ray–depleted BMCs and peripheral blood mononucleated cells (PBMCs), which in turn impaired induction of uncoupling protein 1 (UCP1) through administration of β3 adrenergic receptor agonist, CL 316, 243 (CL), in inguinal white adipose tissue (iWAT). In contrast, CL‐induced UCP1 induction in brown adipose tissue was unaffected by BMC depletion. Transplantation of normal BMCs into mice depleted of BMCs recovered PBMC levels and rescued the ability of iWAT browning by CL. Furthermore, analyses of mice transplanted with green fluorescent protein (GFP)‐labeled BMCs revealed that the number of GFP‐positive BMCs and PBMCs were significantly decreased by CL and that GFP‐positive stromal cells and GFP‐positive UCP1‐expressing multilocular adipocytes appeared in iWAT after CL administration, demonstrating differentiation of BMC‐derived preadipocytes into UCP1‐expressing thermogenic adipocytes. These results unveiled a crucial role of the BMC as a nonresident origin for a subset of thermogenic adipocytes, contributing to browning of white adipose tissue.—Yoneshiro, T., Shin, W., Machida, K., Fukano, K., Tsubota, A., Chen, Y., Yasui, H., Inanami, O., Okamatsu‐Ogura, Y., Kimura, K. Differentiation of bone marrow‐derived cells toward thermogenic adipocytes in white adipose tissue induced by the β3 adrenergic stimulation. FASEB J. 33, 5196–5207 (2019). www.fasebj.org